Choice without Inclusion?: Comparing the Intensity of Racial Segregation in Charters and Public Schools at the Local, State and National Levels - Julian Vasquez Heilig; T. Jameson Brewer; Yohuru Williams (Education Sciences, 2019)
We conduct descriptive and inferential analyses of publicly available Common Core of Data (CCD) to examine segregation at the local, state, and national levels. Nationally, we find that higher percentages of charter students of every race attend intensely segregated schools. The highest levels of racial isolation are at the primary level for public and middle level for charters. We find that double segregation by race and class is higher in charter schools. Charters are more likely to be segregated, even when controlling for local ethnoracial demographics. A majority of states have at least half of Blacks and a third of Latinx in intensely segregated charters. At the city level, we find that higher percentages of urban charter students were attending intensely segregated schools.